2021
DOI: 10.1109/comst.2020.3033665
|View full text |Cite
|
Sign up to set email alerts
|

The Security Reference Architecture for Blockchains: Toward a Standardized Model for Studying Vulnerabilities, Threats, and Defenses

Abstract: Blockchains are distributed systems, in which security is a critical factor for their success. However, despite their increasing popularity and adoption, there is a lack of standardized models that study blockchain-related security threats. To fill this gap, the main focus of our work is to systematize and extend the knowledge about the security and privacy aspects of blockchains and contribute to the standardization of this domain.We propose the security reference architecture (SRA) for blockchains, which ado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 185 publications
(324 reference statements)
0
48
0
2
Order By: Relevance
“…The low number of filtered results can be attributed to the fact that many papers mention or cite existing vulnerabilities and attacks, but do not contribute new vulnerabilities. We conducted additional in-depth research on each of the found attacks by searching for the attack's name, which yielded additional literature [4], [7], [18].…”
Section: Attacks and Threat Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low number of filtered results can be attributed to the fact that many papers mention or cite existing vulnerabilities and attacks, but do not contribute new vulnerabilities. We conducted additional in-depth research on each of the found attacks by searching for the attack's name, which yielded additional literature [4], [7], [18].…”
Section: Attacks and Threat Indicatorsmentioning
confidence: 99%
“…If several Orderer Admins collude, they may attempt to rewrite the blockchain in an Alternative History attack [7], [20]. This requires > 50% of nodes to collude (crash-fault tolerance), or > 2f nodes for byzantine-fault tolerant consensus where 3f + 1 nodes tolerate f malicious nodes.…”
Section: B Malicious Intentmentioning
confidence: 99%
See 1 more Smart Citation
“…Un aspecto fundamental para entender el funcionamiento de esta tecnología es su ecosistema, esto es, el conjunto de sujetos que hace posible su funcionamiento e intervienen en mayor o menor medida en el sistema (Homoliak et al, 2019). Blockchain es una base de datos que conserva no solo el estado final del registro, sino el historial completo de transacciones realizadas.…”
Section: Tecnología Blockchainunclassified
“…Existen también los nodos validadores, que a diferencia de los mineros solo pueden leer el contenido de la cadena de bloques, pero no escribir en ella. Su función es dar soporte al sistema, siendo una parte más de estas copias distribuidas y comprobar el correcto funcionamiento de la red (Homoliak et al, 2019).…”
Section: Tecnología Blockchainunclassified